Operating characteristics research of twin-screw refrigeration compressor with different refrigerants based on the semi-empirical model - 李彦澎; 陈浙寅; 王闯; 任大伟; 邢子文; 朱士哲 (Zhileng xuebao)
The refrigeration field has moved into a new period of finding environmentally friendly, efficient, and safe alternative refrigerants. To analyze the compressor operating characteristics when adopting different refrigerants, a modified semi-empirical model with 13 characteristic parameters is proposed in this paper. Subsequently, a performance experiment of R22, R507, and R744 under variable operating conditions was carried out for parameters identification and model validation. A good agreement between the experimental and simulated values is attained, with average relative errors of 2.07% and 1.17% for input power and mass flow rate. Taking a typical working condition as an example, the change trends of losses and efficiencies of different refrigerants with frequency have been carefully compared and analyzed. Conclusions show that, with the lowest pressure loss, leakage, and power loss, R744 has the best overall performance. The performance of R507 and R22 is similar, while the efficiency of the former decays significantly and is lower at frequencies over 50 Hz, because of the higher and more sharply increasing pressure losses. The purpose of this study is to provide the theoretical basis for the optimization design of the compressor’s physical structure with different refrigerants.